2004
DOI: 10.1016/j.ehj.2003.10.024
|View full text |Cite
|
Sign up to set email alerts
|

Overweight and obesity in patients with established coronary heart disease: Are we meeting the challenge?

Abstract: These results suggest that the growing population of overweight and obese coronary patients is at particularly high risk for further cardiovascular complications due to elevated risk factor levels on the one hand and their insufficient therapeuticcontrol on the other hand. Our results also confirm the considerable weight gain seen in a high proportion of patients following their cardiac event.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
37
1
4

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 41 publications
(45 citation statements)
references
References 22 publications
3
37
1
4
Order By: Relevance
“…In another analysis of over 5500 patients recently diagnosed with CAD from 15 European centers, weight changes at least 6 months after coronary disease seemed to be equally distributed between gains and losses, with the population distribution similar to a normal curve and the majority of patients experiencing very little weight change (mean weight loss was not reported). 41 Thus, we are confident that in this relatively short time span, substantial changes in weight were unlikely to occur. It should also be recognized that because we compared HRQOL between BMI groups, differential changes in weight would have had to occur between BMI groups to bias the results.…”
Section: Discussionmentioning
confidence: 99%
“…In another analysis of over 5500 patients recently diagnosed with CAD from 15 European centers, weight changes at least 6 months after coronary disease seemed to be equally distributed between gains and losses, with the population distribution similar to a normal curve and the majority of patients experiencing very little weight change (mean weight loss was not reported). 41 Thus, we are confident that in this relatively short time span, substantial changes in weight were unlikely to occur. It should also be recognized that because we compared HRQOL between BMI groups, differential changes in weight would have had to occur between BMI groups to bias the results.…”
Section: Discussionmentioning
confidence: 99%
“…It is thus not surprising that recent statistics have shown that about a quarter of adults in the USA [4] and in Switzerland [7] have the metabolic syndrome. Obese patients with metabolic syndrome, overt diabetes mellitus, and hypertension are at high risk for cardiovascular complications mostly by an induced endotheliumdependent dysfunction [1,3,[8][9][10]. It has been shown that, in obese patients with type 2 diabetes, orlistat induces weight loss and improves glycemic control and lipid profile without negative effects on mortality [11][12][13].…”
Section: Introductionmentioning
confidence: 99%
“…At any time, about 45% of the women and 30% of the men in the USA are actively seeking to lose weight, in most cases to no avail [3,5,6]. Similar results have been reported for Europe [3,7] where despite these efforts the prevalence of overweight and obesity even in patients with established heart disease is still sharply rising at an even more pronounced rate than in the general population [3]. It is thus not surprising that recent statistics have shown that about a quarter of adults in the USA [4] and in Switzerland [7] have the metabolic syndrome.…”
Section: Introductionmentioning
confidence: 99%
See 2 more Smart Citations